PEMBERDAYAAN FAKIR MISKIN OLEH DINAS SOSIAL KOTA SEMARANG: ANALISIS TAHAPAN PEMBERDAYAAN DAN FAKTOR-FAKTOR YANG MEMENGARUHINYA - Yosafhat Manalu; R. Slamet Santoso (Journal of Management and Public Policy, 2026)
Poverty remains one of the persistent social challenges faced by local governments, including Semarang City. The paradox between the city's high economic achievements and the 119.04% surge in the number of the poor to 63,091 individuals in 2024 indicates that existing empowerment programs have yet to produce optimal economic independence. This study aims to analyze the stages of empowerment of the poor implemented by the Semarang City Social Service (Dinas Sosial) and to identify the factors influencing its implementation. A qualitative descriptive research method was employed, with data collected through observation, in-depth interviews, and documentation. Informants were selected using purposive and snowball sampling techniques, consisting of Social Service officials, PKH facilitators, district social workers (TKSK), and beneficiaries. The findings reveal that empowerment is carried out through three stages: the awareness stage, the capability transformation stage, and the intellectual capacity enhancement stage. At the awareness stage, beneficiaries began to recognize their own potential, although their understanding of poverty remains oriented toward short-term social assistance. At the capability transformation stage, vocational training through the Joint Business Group (KUBE) has enabled some beneficiaries to engage in productive activities, yet its application remains inconsistent due to challenges in business management and marketing. At the intellectual capacity enhancement stage, some beneficiaries have begun to make independent economic decisions, though the ability to systematically develop business plans has not been evenly distributed. The factors influencing the empowerment process include natural resources, human resources, institutional conditions, infrastructure, policy, and organizational administrative aspects. Low quality of human resources among the poor and budget constraints constitute the most significant obstacles. Strengthening post-program mentoring, improving managerial capacity, and updating the DTKS data are recommended to make the empowerment of the poor more effective and sustainable.